Studi Evaluatif Metode PCI dan SDI untuk Penilaian Kondisi Jalan Lengkong-Jatikalen - Fatardhoo, Abroor Kissraya; Winarto, Sigit; Komari, Ana (Universitas Batanghari Jambi, 2025)
Nganjuk Regency is currently facing significant challenges related to road infrastructure damage, which hinders the distribution of agricultural products. This study aims to evaluate and compare the effectiveness of Two methods used to assess pavement condition are the Pavement Condition Index (PCI) and the Surface Distress Index (SDI), applied to the Lengkong–Jatikalen road segment. A quantitative descriptive approach with a case study method was employed. Data were collected through field surveys and traffic observations. The observed average daily traffic volume reached 5,640 vehicles per day, equivalent to 2,934 passenger car units (PCU) per day, indicating a high traffic category. The dominant types of damage were alligator cracking (49%), potholes (28%), and patches (11%). The evaluation results showed an average PCI value of 64.4 (good condition) and an SDI value of 38.6 (good condition). Differences between the PCI and SDI methods are evident in certain segments, such as STA 0+100–0+200, which received a PCI score of 48 (fair) and an SDI score of 65 (moderate), and STA 0+000–0+100, which received a PCI score of 44 (fair) and an SDI score of 25 (good). Both methods provide different insights into road conditions, with PCI being more sensitive to complex damage and more suitable for long-term planning, while SDI is more efficient for quick field inspections. Maintenance recommendations include routine maintenance for minor damage and partial reconstruction for subsidence damage. This research can serve as a foundation for more efficient and sustainable road maintenance planning.